Effect of Zn substitution in Cr3+ doped MgAl2O4 mixed spinel nanoparticles on red/NIR emission properties. (March 2019) - Karthik H.G., Shreekrishna; Menon, Samvit G.; Hebbar N., Deepak; Choudhari, K.S.; C., Santhosh; Kulkarni, Suresh D.
Graphical abstract: Highlights: Solid-solution of red emitting Mg1-x Znx Al1.98 Cr0.02 O4 nanoparticles were prepared. Particles were smaller (38 nm) in Mg-rich samples & bigger (58 nm) in Zn-rich samples. PL showed intense R-line for x = 0.5 & sidebands were pronounced with Zn content. High Dq/B (3.5–3.9) but unaffected by Zn content imply Cr 3+ in strong crystal field. Lifetimes (25–34 ms) suggest their use in bio-imaging & optoelectronic applications. Abstract: Red/Near-infrared (NIR) emitting Mg1-x Znx Al1.98 Cr0.02 O4 nanoparticles were synthesized by co-precipitation followed by firing(1200 °C). Gradual shift of XRD peaks with Zn-content confirmed complete solid-solution formation. HRTEM revealed hexagonal sheet-like structures and lattice fringes revealed their single-crystallinity. Owing to refractory nature of MgAl2 O4, particles were smaller(∼38 nm) in Mg-rich samples and gradually increased(∼58 nm) with Zn-substitution. Due to trigonal distortion, the fine splitting of the 4 T1g level of Cr 3+ manifests as asymmetric band(400 nm) in the excitation spectrum. Cr 3+ emission was clearly observed, comprising of R-line and multi-phonon side-bands on either side, with maximum R-line intensity for x = 0.5. With increasing x, side-bands were more pronounced probably due to the band-gap difference of end members. High Dq/B (3.5–3.9), suggested Cr 3+ in a strong crystal-field. Racah-parameter(B) variations suggest increased electron delocalization over molecular orbitals for higher Mg 2+ substitutions. Longer lifetimes (23–34 ms) are well-suited for bioimaging and optoelectronic applications. Such a simple synthesis can be easily extended to other important phosphors.